03 Women Imagery in Folk Wedding Songs:An Ethnographic Study of Rajput Folksongs (Journal of Gender and Social Issues, 2018)
Folksongs play an important role in the social construction of identity as well as cultural promotion of particular areas. As an oral tradition, Folksongs are unlimited in their forms and subject-matters that ranging from simple to complex. The objectives of this ethnographic research are to investigate analysis and interpret Rajput women folk wedding songs as explicated by Rajput women themselves in their cultural context. The research conducted in a village, Wahando, near Gujranwala (Punjab, Pakistan) where many Rajputs families live. The research methods used is in-depth interviews through which eight women are interviewed and twenty folk wedding songs collected from them. Most of the songs collected from a mirassan (a professional singer) locally known as Dadi who sings folk wedding songs, other songs narrated by women of the family and written by the researchers. However, men perspectives about folksongs limit the study…
Keywords: Women; Folksongs; Rajput; Wedding; Birth songs